Neuralgic amyotrophy complicating acute hepatitis E infection: a rare association. (4th March 2015) - Theochari, Evangelia; Vincent-Smith, Lisa; Ellis, Cathy
Abstract : Hepatitis E virus infection (HEV) is an emerging pathogen that is under-recognised in developed countries. Preceding infection manifested by acute transaminitis has been associated with neurological manifestations, predominately involving the peripheral nervous system, even in immunocompetent patients. We present a case of a 65-year-old previously fit and well Caucasian man with bilateral neuralgic amyotrophy (NA) and acute transaminitis. Serology testing for immunoglobulin (Ig) M and G established the diagnosis of acute HEV infection. The patient received immunomodulatory treatment with an excellent long-term outcome. The temporal association of the clinical presentation of bilateral NA and acute transaminitis from HEV infection suggested the causal association of HEV to NA. We propose screening for HEV in patients presenting with NA and acute hepatitis.